2007
DOI: 10.1111/j.1349-7006.2007.00436.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the DNA repair gene XRCC1 associated with basal cell carcinoma and squamous cell carcinoma of the skin in a Korean population

Abstract: (1-5) DNA repair enzymes are involved in repairing damaged DNA and at least four pathways operate on specific types of DNA damage: the BER, (6)(7)(8) NER, (9) DSBR (10,11) and MMR (12) pathways. Enzymes involved in BER include XRCC1, those involved in NER include XPC, XPD, ERCC1, those involved in DSBR include BRCA1, BRCA2 and XRCC3, and those involved in MMR include MLH1, MSH2, PMS2 and MSH6. Polymorphisms of DNA repair genes may also alter protein function and the capacity to repair damaged DNA, which may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 36 publications
(55 reference statements)
1
22
0
Order By: Relevance
“…It was suggested that the XRCC1 Arg399Gln polymorphism was also associated with other cancers in Asian population, which included colorectal cancer, 42 lung cancer, 43 basal cell carcinoma 44 and so on. The study by Wang et al 42 indicated that the XRCC1 399Gln allele was associated with a significantly increased rectal cancer risk among men.…”
Section: Xrcc1 Polymorphisms and Prostate Cancer Risk B Wei Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…It was suggested that the XRCC1 Arg399Gln polymorphism was also associated with other cancers in Asian population, which included colorectal cancer, 42 lung cancer, 43 basal cell carcinoma 44 and so on. The study by Wang et al 42 indicated that the XRCC1 399Gln allele was associated with a significantly increased rectal cancer risk among men.…”
Section: Xrcc1 Polymorphisms and Prostate Cancer Risk B Wei Et Almentioning
confidence: 99%
“…Besides, XRCC1 Arg399Gln polymorphism may alter the risk of lung cancer in women nonsmokers in China. 43 Kang et al 44 found that the XRCC1 Arg399Gln polymorphism was associated with an increased risk of basal cell carcinoma. 44 Given the important roles of XRCC1 gene, it is biologically plausible that XRCC1 polymorphism may modulate the risk of PCa.…”
Section: Xrcc1 Polymorphisms and Prostate Cancer Risk B Wei Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Mixed results were also obtained for other cancer entities. While a protective effect of the XRCC1 variant has been reported for nasopharyngeal carcinoma ) and squamous cell carcinoma (Kang et al 2007), an increased risk was observed for salivary gland carcinoma (Ho et al 2007). For alleles 280 and 399, no significant association between the variant form and risk of cancers including lung cancer (Hao et al 2006;Hung et al 2005;Yin et al 2009), salivary gland carcinoma (Ho et al 2007) and nasopharyngeal carcinoma ) is reported, suggesting that the XRCC1 SNPs at position 280 and 399 do not play a major role for cancer risk.…”
Section: Snps In Xrcc1mentioning
confidence: 97%
“…For alleles 280 and 399, no significant association between the variant form and risk of cancers including lung cancer (Hao et al 2006;Hung et al 2005;Yin et al 2009), salivary gland carcinoma (Ho et al 2007) and nasopharyngeal carcinoma ) is reported, suggesting that the XRCC1 SNPs at position 280 and 399 do not play a major role for cancer risk. On the other hand, an increased cancer risk for the variant form of allele 399 was reported for squamous cell carcinoma (Kang et al 2007) and lung cancer (De Ruyck et al 2007;Wang et al 2015).…”
Section: Snps In Xrcc1mentioning
confidence: 99%